LANGUAGE LEARNING AS A COGNITIVE ENHANCEMENT STRATEGY AMONG KURDISH EFL LEARNERS IN CHARMO UNIVERISTY, CHAMCHAMAL, KURDISTAN REGION, IRAQ - Mahmood, Khelan Mohammed Salih; Mohammed, Zana Othman; Murad, Ibrahim Mohammed Ali (Universitas Islam Sumatera Utara (UISU), 2025)
The current mixed-methods study focuses on cognitive enhancement strategies through Structured English as a Foreign Language (EFL) learning among fourth-year students at Charmo University, Chamchamal, Iraq. The study considers the implications consequent to the cognitive flexible triggering of problem-solving, resilient psychologically from the translated memorized content, and acquisition of a foreign language. The study revealed quantitative results of strong positive interrelations of language learning with cognitive enhancement (r = 0.614, p < 0.05 medium effect), adaptive cognitive functioning (r = 0.643, p < 0.05) and resilience psychologically (r = 0.597, p < 0.05). The qualitative analysis on thematic analysis and semi-structured interviews illustrated the students’ self-reported mental flexibility, creativity, and cultural awareness, as well as the positive adjustments from the anxiety. There are no significant differences in gender (p > 0.05). The study principally highlighted the cognitive advantage of advanced EFL learning, countering claims of diminished bilingual advantage over time. Integration of culturally relevant language materials into higher education curricula will serve as cognitive training, considering the scarce studies on the neuropsychological benefits of language learning within the context of developing countries.